Analisis Historis Implementasi Kebijakan Fiskal di Era Pemerintahan Abu Bakar dan Umar Bin Khattab dan Relevansinya bagi Indonesia - Nisa, Fadhilatun; Sari, Khalila Husna; Atmadi, Agri; Arkan, Farras; Hidayat, Faisal (Yayasan Lembaga Studi Makwa, 2023)
This study analyzes the implementation of fiscal policy during the reigns of Abu Bakr and Umar bin Khattab and its relevance to Indonesia today. Fiscal policies during these two caliphs played a crucial role in establishing economic stability and societal welfare through fair distribution systems, optimization of state revenues, and efficient budget management. Abu Bakr focused on restoring financial stability after the passing of the Prophet Muhammad, while Umar bin Khattab introduced more systematic fiscal reforms, including the establishment of the Baitul Mal as the central financial administration institution and resource distribution policies for public welfare. This study employs a qualitative method with a historical-comparative approach to explore how the fiscal principles applied during Abu Bakr and Umar bin Khattab's leadership can be adapted to Indonesia's economic context. The findings indicate that the concepts of transparency, social justice, and efficiency in state financial management implemented by these caliphs have relevance to Indonesia’s modern fiscal policies, particularly in tax management, social subsidies, and budget stabilization. By integrating Islamic fiscal principles with contemporary economic challenges, Indonesia can adopt a more inclusive and equitable approach to fiscal policy. This study provides insights for policymakers in designing more effective fiscal strategies that balance economic growth and social welfare.